Microbial diversity in Catba island. Part 1: the number and distribution - Hien, Lai Thuy; Nga, Vuong Thi; Yen, Nguyen Thi; Tu, Nguyen Ba (Academia Journal of Biology, 2014)
Catba one of the world biosphere reserves admitted by UNESCO in 2004 consists 367 islands located in Lanha bay and contains all biodiversity-reserved values. Despite the number of scientific reports focus on the diversity of Catba marine animals and plants, valuable researches on microbial communities, which play an essential role in nature element cycles and have many potential uses, is still lacking. Recently, we have carried out a survey to assess the microbial potential in Catba marine water. The analyzed data on microorganisms in Catba marine water and sediment showed that the distribution and the quantity of each individual microorganism were different according to the depth: the quantities of microorganisms in the sediment samples were higher than those in the marine water samples from 10-103 fold. The number of each microorganism was various: 105 - 3.4 ´ 107 aerobic, 104 - 107 fermentative, 104 - 5 ´ 105 hydrocarbon utilizing, 101 - 5 ´ 105 sulfate-reducing and 101 - 106 nitrogen conversion bacteria. Fungi and yeast are present in only few collected samples with low number. Classification of the dominant microorganisms based on their morphology, chemo taxonomy or 16S r RNA sequence analysis exhibited that they are belonging to the species: Acinetobacter johnsonii, Pseudomonas vesicularis, Pseudomonas aeruginosa, Pseudomonas cepacia, Flavobacterium indologenes, Sphingomonas paucimobilis, Ochrobactrum cytisis, Janibacter marinus, Bacillus megatherium, Cladosporium spherospermum, Penicillium oxalicum, Candida parasilosis and Rhodotorula musilaginosa, Streptomyces celluloflavus, Streptomyces sclerotialus. This preliminary result is important step towards applying the useful microorganisms for environmental pollution control and limiting the effect of harmful microorganisms.